Penguatan Kapasitas Santri dalam Memahami Al-Qur’an dengan Terapan Jumlah Syarthiyyah di Pondok Pesantren Roudlatut Tholibin Metro Lampung - Nur Amin, Muhammad; Nur, Kholida; Zarnuji, Ahmad; Haikal, Haikal; Fadilah, Fitria Nurul; Azizah, Isnaiani Nur (Bulletin of Community Engagement, 2023)
Assistance in understanding the Koran is an essential activity. This program is one of the instructions for achieving services, namely training in studying the Al-Qur'an through the application of Total Syarthiyyah. This article supports strengthening the capacity of students in understanding the Al-Qur'an which has been implemented at the Roudlotul Thalibin Islamic boarding school in Metro Lampung. The method used in mentoring is Service Learning (SL) as a medium for integrating voluntary community service with active reflection which is expected to enrich and strengthen the material that will be delivered using the use of existing assets and potential. Data collection uses interviews, observation and documentation. The sample was taken from 35 students. The results show that the capacity of students to understand the Al-Qur'an with the application of Total Syarthiyyah can be understood. The researcher's findings are that there are still many students who cannot understand the Al-Qur'an which is based on correct Arabic language rules. Next, the researchers will provide solutions for people who want to understand the Qur'an by applying Total Syarthiyyah Keywords: Strengthening the Capacity of Santri, Understanding the Qur'an, Syarthiyyah